PENGARUH METODE PEMBELAJARAN TEAM ACCELERATED INSTRUCTION TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII SMP - Fatimah, Ta; Abidin, Zainal (Media Pendidikan Matematika, 2016)
The problem in mathematics learning at SMPN 3 Praya Barat Daya is that the teacher still apply conventional method so that the passive student in the class, lack of understanding the material explained and the lack of interaction between the student in solving the given problem. As a result students’ mathematics learning achievement becomes low. Therefore, the purpose of this research is to know the influence of Team Accelerated Instruction method toward student’s mathematics learning achievement. Team Accelerated Instruction method is a method of learning where students learn in small groups that are heterogeneous followed by the provision of individual assistance to students who need, so that students are more active in learning activities of mathematics. This study aims to determine the effect of team accelerated instruction method toward students mathematics learning achievement at VII grade of SMPN 3 Praya Barat Daya in academic year 2016/2017. The type of research used in this study is Experiments. The experimental design used was Quasi Eksperimen. The research design was nonequivalent control group design, the population in this study were the students of grade VII SMPN 3 Praya Barat Daya, the sample used was the students of class VII.A which amounted to 24 people as the control class and the students of class VII.B which amounted to 21 people as class experiments and sampling techniques using saturated sampling, data collection techniques using essay-shaped tests to obtain data on student learning outcomes. Based on the result of data analysis obtained by Zhitung equal to 7,14 at 5% significant level whereas Ztabel obtained is 0,0000. So the result of U-test that is Zhitung> Ztabel that is 7,14> 0,0000. Hence can be concluded that There is Influence Method Of Team Accelerated Instruction towartd student mathematic achievement VII grade of SMPN 3 Praya Barat Daya in academic year 2016/2017